Legal protection of victims of domestic violence in Republika Srpska - Marković Ivanka (Temida)
Legal protection of victims of domestic violence in Republika Srpska is analyzed in this work. With regard to the above, the author highlights that in Republika Srpska there are two forms of legal protection from domestic violence they fall within the remit of criminal law and misdemeanor law. Introduction of such protection model was intended for the protection of victims from this form of violent behavior, which is, by its characteristics a specific form of criminal behavior and as such demands special measures of lawful reaction by the state. Protection of victims of domestic violence falling within the remit of criminal law, which is very important since it attaches the same gravity to this and the other forms of criminality giving it a certain degree of criminal-political weight, has not produced expected results. For that reason was adopted a special Law on Protection from Domestic Violence defining the notion of domestic violence, persons considered to be a family members, methods of their protection, as well as the kind and purpose of misdemeanor law related norms with emphasizing the fact that all the proceedings initiated under this law are of an urgent nature. The main driving force leading to the adoption of this Law is to obtain a complete and systematic regulation of domestic violence to enable faster, more efficient and durable protection of the endangered persons. The most important thing about this Law on Protection from Domestic Violence is introduction of protective measures, which could be sentenced against the perpetrator and which, in fact, allow for the protection of victims to family violence. Method of its concrete implementation regulated is by the relevant by-laws. Adoption of law sanctioning domestic violence, either as a criminal act or as a misdemeanor, together with the adoption of by-laws for the implementation of particular protective measures, represent a step forward in combat and prevention of domestic violence. However, the author emphasizes that, despite such normative solutions, we still cannot talk about some important results achieved in the area of combat and prevention of domestic violence. Therefore, a wide-scope action was initiated on the territory of Republika Srpska in the direction not only of combating of family violence, but also finding and eradication of reasons and causes of negative social manifestation. The final goal of this activity is protection of victims, prevention of violence and preservation of a healthy family as a basis of society.